ANALYSIS OF TILT ANGLE AND BATTERY CHARGING TIME OF ELECTRICAL POWER REQUIREMENTS FOR WOOD CUTTING EQUIPMENT PURPOSES - Sandy Suryady; RR. Sri Poernomo Sari (International Journal Science and Technology, 2022)
Solar panels are a tool that serves to convert sunlight into electrical voltage, sunlight itself contained energy in the form of photons. In this photon hit the surface of the electron solar cell panel that will be excited and cause electricity. This is known as the photoelectric principle. Every day the earth rotates on its axis while orbiting along the ellipse. Where along the plane of the earth's orbit is called the ecliptic plane so that it affects the geothermal received. So in this study analyzed the angle of the panel with the battery charging time needed on wood cutting equipment. From the results of testing and observation of the most effective tilt angle and with the highest power is an angle of 30°. Where the intensity of sunlight received by solar panels is very influential that determines the amount of electrical output or power generated by solar panels. Due to erratic weather and average power generated during 7 hours of measurement and observation produces 55.29 Watts then the power passed on the scc (controller) for the battery charging time for 7 hours then (7 hours × 55.29 Watt = 387.03 Watts / h) after being calculated to get a total load of 328.98 Wh and the length of battery charging time at full condition (full) is 1.64 Hours (h) with the slope angle sample taken is an angle of 30° with power highest.